Prevalence of Tuberculosis among health care workers in a tertiary teaching hospital in Malaysia - Ahmad Farid Nazmi Abdul Halim,; Mohd Rohaizat Hassan,; Sharifah Azura Salleh,; Nor Rina Mahawar, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Health care workers are at increased risk of nosocomial transmission of tuberculosis (TB). This study aimed to determine the prevalence of TB among health care workers and its associated factors. A retrospective analysis was conducted using database of TB screening program at Hospital Canselor Tuanku Mukhriz (HCTM) over the period of three years (2018-2020). The prevalence rate of TB showed increasing trend, from 1.54 per 100 health care workers in 2018 to 5.02 per 100 health care workers in 2020. Aged group of 31-40 had higher risk for contracting TB B (p<0.001), health support workers had significant association with TB acquisition (p=0.008), workers in Diagnostic Laboratory Department had the high risk of getting infected with TB (p<0.001) and the workplace with the highest prevalence was in laboratory (45.9%). In terms of TB index cases among health care workers, 16 cases (69.5%) were pulmonary tuberculosis (PTB), 6 cases (26.1%) were extrapulmonary tuberculosis (EPTB) and 1 case (4.4%) had both PTB and EPTB. It was crucial for health care workers to be aware of these significant associations and for relevant authorities to carry out protective measures.